2021
DOI: 10.1038/s41598-021-94429-5
|View full text |Cite
|
Sign up to set email alerts
|

Simulated transient hearing loss improves auditory sensitivity

Abstract: Recently, it was proposed that a processing principle called adaptive stochastic resonance plays a major role in the auditory system, and serves to maintain optimal sensitivity even to highly variable sound pressure levels. As a side effect, in case of reduced auditory input, such as permanent hearing loss or frequency specific deprivation, this mechanism may eventually lead to the perception of phantom sounds like tinnitus or the Zwicker tone illusion. Using computational modeling, the biological plausibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…For instance, in a theoretical study it could be demonstrated that stochastic resonance improves speech recognition in an artificial neural network as a model of the auditory pathway (Schilling et al, 2020 ). Very recently, we were even able to show that stochastic resonance, induced by simulated transient hearing loss, improves auditory sensitivity beyond the absolute threshold of hearing (Krauss and Tziridis, 2021 ). The extraordinary importance of resonance phenomena for neural information processing indicates that the brain, or at least certain parts of the brain, do also actively exploit other kinds of resonance phenomena besides classical stochastic resonance.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a theoretical study it could be demonstrated that stochastic resonance improves speech recognition in an artificial neural network as a model of the auditory pathway (Schilling et al, 2020 ). Very recently, we were even able to show that stochastic resonance, induced by simulated transient hearing loss, improves auditory sensitivity beyond the absolute threshold of hearing (Krauss and Tziridis, 2021 ). The extraordinary importance of resonance phenomena for neural information processing indicates that the brain, or at least certain parts of the brain, do also actively exploit other kinds of resonance phenomena besides classical stochastic resonance.…”
Section: Discussionmentioning
confidence: 99%
“…By propagating the additional noise upstream to the auditory cortex, the signal is there interpreted as a sound – the perceived tinnitus. This idea is strengthened by another recent animal study ( Krauss and Tziridis, 2021 ) where simulating HL by reducing the loudness of specific frequencies – similar to a Zwicker tone ( Zwicker, 1964 ) – leads to a transient tinnitus percept and better hearing thresholds. Further additional support of this view gives the demonstration that tinnitus patients seem to have better hearing thresholds in the – for human communication important – frequency range up to 3 kHz compared to patients without such a phantom percept ( Gollnast et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have proposed theoretical models based on stochastic resonances, which argue that adding neuronal internal noise to the system can counteract hidden and/or non-hidden hearing loss, and the development of a tinnitus percept is a side effect of this process ( Krauss et al, 2016 , 2018 ; Krauss and Tziridis, 2021 ; Schilling et al, 2021 ). Stochastic resonance models can explain some of the results of this study.…”
Section: Discussionmentioning
confidence: 99%